Supervisory Layer for Improved Interactivity of Distributed Generation Inverters with Smart Grids - Emerson Giovani Carati; Victor Emanuel Soares Barbosa; Rafael Cardoso; Carlos Marcelo de Oliveira Stein; Jean Patric da Costa (Journal of Sensor and Actuator Networks, 2021)
This work proposes an autonomous management system for distributed generation (DG) systems connected to the AC grid, using supervisory control theory (SCT). SCT is used to deal with discrete asynchronous events that modify the properties and operational conditions of these systems. The proposed management layer allows the smart inverters to interact with smart grid managers (SGMs), while guaranteeing operation compliance with the IEEE Standards. The implemented supervisor for the management layer is an automaton that performs the smart inverter manager (SIM) functions in the photovoltaic systems in discrete events. A DSP real-time verification was performed with Typhoon HIL 602+ to demonstrate the smart inverter’s operating dynamics connected to the grid. The results showed the fast response and robust operation of the smart inverter manager to the commands from the smart grid manager.